Impact of EV on the Icelandic power system : a general analysis and cost estimate - Hákon Valur Haraldsson 1992- (2020)
The increasing problem of reducing global warming has lead to a demand for less polluting transport, this is usually in the form of Electric vehicles. But what impact do larger percentages of EVs have on both pollution and on the power system in general? This study aims to answer some of the questions as they relate to these problems in Iceland - what is the total benefit in greenhouse gas emissions and more importantly what is the total cost for the Icelandic power system in relation to system upgrades, and how do we estimate it? The entire Icelandic power system was simulated in MATPOWER using two models (the current system and a future development plan) and several methods for estimating both the cost of system upgrades and what part the electric load from EVs had in that cost. The results show which parts of the system need to be upgraded and when. Finally the cost for each simulated case is summarised and put forth as a total number. It can be concluded that the cost of increasing EVs is considerable in worst case scenarios where future location of power production uncertainty are taken into account. Hnattræn hlýnun er vaxandi vandamál sem hefur leitt til eftirspurnar á farartækjum sem menga minna, yfirleitt eru það rafbílar sem verða fyrir valinu. En hvaða áhrif hefur hátt hlutfallrafbíla á bæði mengun og raforkukerfið í heild sinni. Þessi rannsókn reynir að svara einhverjum af þessum spurningum miðað við hvernig hlutirnir eru hér á Íslandi, hver er heildar ávinningurinn í minnkun gróðurhúsalofttegunda og það sem er líklega mikilvægara er að áætla kostnaðinn við að styrkja Íslenska raforkukerfið. Allt Í íslenska raforkukerfið var hermt í MATPOWER með tveimur módelum (núverandi kerfi og kerfisáættlun Landsnets) svo var nokkrum aðferðum beitt til að áætla kostnaðinn við styrkingar á kerfinu og hversu stóran þátt álagið frá rafbílunum átti í þeim kostnaði. Niðurstöðurnar sýna hvaða hluta kerfisins þarf að styrkja og hvenær. Að lokum er kostnaður fyrir hvert hermt tilvik dreginn saman og settur fram sem loka ...